PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - TRIATMAJA, FACHTURAHMAN (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
This study aims to determine and analyze the influence of capital structure and the size of the company on the company values in manufacturing companies of food and beverage industry sectors listed on the Indonesia Stock Exchange (BEI). The sample in this study consists of 11 companies that selected by purposive sampling technique. Method of data analysis is multiple linear regression using SPSS version 16.0. The results show that both independent variables simultaneously have positive and significant influence on value of the company with sig-F of 0.093 ? ? 0.10 at confidence level of 90%. The t-test shows that the capital structure significantly has negative influence on the value of the company with sig-t of X1 = 0.032 ? ? of 0.10 and beta value of -0882. While the company size has non-significant influence on the value of the company with sig-t X2 = 0.787 ? ? of 0.10 with R2 values of 0.052 or 5.2%. Both independent variables studied simultaneously influence the dependent variable (enterprise value), while the remaining 94.8% is influenced by other variables that are not studied.